Cultural attitudes and their impact on social exchanges, self-compassion, and mental health during pregnancy - Al-Mutawtah, Mona; Erjavec, Mihela; Kubis, Hans-Peter (Frontiers in Psychology, 2025)
IntroductionPregnancy is a crucial period for women’s physical and mental health, influenced by cultural attitudes and social relationships. This study explores how cultural orientations, social exchanges, and self-compassion interact to shape stress and depression during pregnancy, drawing on cultural psychology, social exchange theory, and stress-coping frameworks.MethodsA cross-sectional survey was conducted with 280 married Kuwaiti pregnant women recruited through convenience sampling. Data were analysed using structural equation modelling (SEM) to examine relationships among cultural attitudes (individualism and collectivism), social exchanges, self-compassion, perceived stress, and depression.ResultsIndividualism was positively associated with self-compassion, which in turn reduced stress and depression. Collectivism was linked to higher positive social exchanges, though these did not significantly buffer stress or depression. Negative social exchanges increased perceived stress, which mediated the relationship between negative social exchanges and depression. Planned pregnancy was associated with lower depression scores, while unplanned pregnancies correlated with higher negative social exchanges and greater stress. Higher energy levels significantly decreased depression.DiscussionCultural attitudes play a dual role in maternal mental health. Individualism enhances self-compassion and reduces distress, while collectivism fosters positive support that does not necessarily alleviate stress or depression. These findings emphasise the importance of cultural tailored interventions that integrate self-compassion training with effective social support strategies to promote maternal well-being during pregnancy.